Jezikovne tehnologije od študija do zaposlitve - Fišer, Darja (Jezik in slovstvo, 2005)
The article discusses the need for university syllabi at linguistic departments to be revised in terms of their employment prospects and relevancefor the information society era, which is also the core of the Bologna process. The degree of linguistic and technological topics part of current syllabi is compared with the demands of both employers and linguists. Due to their positive effects on both employers and employees, the article concludes with an illustration of how useful computer tools are for translation studies, therefore pointing out the direction of development of working environments, in which other linguists are also included, and therefore unveiling the needs of the work market to be competent in the area of language technologies.
Keywords: linguistics; lingvistika; univerzitetni študij; študijski programi; zaposlitev; Slovenia; Slovenija